Y-specific amh allele, amhy, is the master sex-determining gene in Japanese flounder Paralichthys olivaceus - Hattori, Ricardo Shohei; Kumazawa, Keiichiro; Nakamoto, Masatoshi; Nakano, Yuki; Yamaguchi, Toshiya; Kitano, Takeshi; Yamamoto, Eiichi; Fuji, Kanako; Sakamoto, Takashi (Frontiers in Genetics, 2022)
Japanese flounder (Paralichthys olivaceus) is an important marine fish species of both fisheries and aquaculture in Northeast Asia. The commercial interest for all-female progenies due to several sex-related traits has prompted basic research on the mechanisms of sex determination in this species. By conducting a linkage analysis of the sex-determining locus, we initially identified 12 microsatellite markers linked to sex in 11 scaffolds, whose localization was restricted to a specific region of linkage group 9. Sequence analysis of this region identified 181 genes based on the UniProt database annotations. Among them, the amh gene was considered a potential candidate for sex determination because this gene is known to have taken over the role of sex determination in many teleosts. An in-depth sequence analysis of both the coding and non-coding regions of amh in XX and XY individuals detected nine SNPs linked with maleness. However, because these substitutions were synonymous, the upstream and downstream regions of amh were also investigated and a male-specific variant with deletions in the promoter region was detected. This truncated Y-specific amh variant was named amhy, and the amh shared by both sexes was named amhx. The association analysis using both females and males of the genotypic sex inferred by the presence/absence of amhy found complete association with phenotypic sex and genotype. Gene expression analysis in larvae derived from a single-pair progeny by quantitative real-time PCR detected amhy transcripts in the larval trunks between 20 and 100 days after hatching only in XY larvae. Localization of amhy by in situ hybridization was detected in presumptive Sertoli cells of XY gonads. Expression of amhx was almost undetectable in both XX and XY genotypes. The induction of a loss-of-function mutation by CRISPR-Cas9 in amhy-induced male-to-female sex reversal, indicated that this gene was necessary for the masculinization of XY individuals. In conclusion, the complete linkage of amhy with males, its early expression in XY gonads before testicular differentiation, and the induction of sex reversal by loss-of-function mutation support the view that amhy is the sex-determining gene in this species.